Long-Term Common Resources Management and Resilience in a Local Community: How Kinosaki Onsen could Quickly Respond to COVID-19? - Ayako MORISHITA; Toshio GOTO (AAOS Transactions)
This paper investigates how a small community in Japan has maintained its common resources for centuries, shedding light on the leadership of family business members over generations to formulate cooperative activities, which is not researched in depth. Focusing on the case of Kinosaki Onsen, Hyogo Prefecture, our literature review and interviews with CEOs of family-owned hot spring inns in operation for centuries, reveal this community of 3,125 habitants developed a governance mechanism of shared hot spring resources to solve the social dilemma starting in the 18th century, which was developed into a community resilience system through their experiences with major earthquakes and other crises, under the leadership of community-embedded family business members over generations, based on their generational social capital in the community. We also discover the community’s prompt response to the COVID-19 pandemic is activated by this cooperative mechanism. Our findings not only endorse Elinor Ostrom’s 8 rules for managing the commons, but also exemplify the importance of the family business both in the common-property resource management and community-based resilience from major crises, which haven’t addressed explicitly either in the literature of family business and/or commons management.